Leukocyte infiltration across the blood-spinal cord barrier is modulated by sleep fragmentation in mice with experimental autoimmune encephalomyelitis - He, Junyun (Fluids Barriers CNS, 2014)
BACKGROUND: We have recently shown that mice with experimental autoimmune encephalomyelitis (EAE) have increased sleep fragmentation (SF) and reduced sleep efficiency, and that the extent of SF correlates with the severity of disease. It is not yet clear whether and how sleep promotes recovery from autoimmune attacks. We hypothesized that SF promotes leukocyte infiltration across the blood-spinal cord barrier, impairs immune regulation, and thus worsens EAE. METHODS: Three groups of C57 mice were studied: Resting EAE; SF EAE with the mice subjected to the SF maneuver 12 h /day during zeitgeber time (ZT) 0–12 h; and naïve controls with neither EAE nor SF. Besides monitoring of the incidence and severity of EAE, the immune profiles of leukocytes in the spinal cord as well as those in the spleen were determined. RESULTS: When analyzed 16 days after EAE induction, at which time the SF was terminated, the SF group had a greater number of CD4(+) T cells and a higher percent of CD4(+) cells among all leukocytes in the spinal cord than the resting EAE group. When allowed to recover to 28 days after EAE induction, the SF mice had lower EAE scores than the resting EAE group. EAE induced splenomegaly and an increase of Gr1(+)CD11b(+) myeloid-derived suppressor cells in the splenocytes. However, SF treatment had no additional effect on either peripheral splenocytes or granulocytes that reached the spinal cord. CONCLUSION: The SF maneuver facilitated the migration of encephalopathic lymphocytes into the spinal cord. Paradoxically, these mice had a better EAE score after cessation of SF compared with mice without SF.